Microbial methane cycling in sediments of Arctic thermokarst lagoons - Sizhong Yang; Sara E. Anthony; Maren Jenrich; Michiel H. in ’t Zandt; Jens Strauss; Pier Paul Overduin; Guido Grosse; Michael Angelopoulos; Boris K. Biskaborn; Mikhail N. Grigoriev; Dirk Wagner; Christian Knoblauch; et al. (Global Change Biology, 2023)
Thermokarst lagoons represent the transition state from a freshwater lacustrine to a marine environment, and receive little attention regarding their role for greenhouse gas production and release in Arctic permafrost landscapes. We studied the fate of methane (CH 4 ) in sediments of a thermokarst lagoon in comparison to two thermokarst lakes on the Bykovsky Peninsula in northeastern Siberia through the analysis of sediment CH 4 concentrations and isotopic signature, methane‐cycling microbial taxa, sediment geochemistry, lipid biomarkers, and network analysis. We assessed how differences in geochemistry between thermokarst lakes and thermokarst lagoons, caused by the infiltration of sulfate‐rich marine water, altered the microbial methane‐cycling community. Anaerobic sulfate‐reducing ANME‐2a/2b methanotrophs dominated the sulfate‐rich sediments of the lagoon despite its known seasonal alternation between brackish and freshwater inflow and low sulfate concentrations compared to the usual marine ANME habitat. Non‐competitive methylotrophic methanogens dominated the methanogenic community of the lakes and the lagoon, independent of differences in porewater chemistry and depth. This potentially contributed to the high CH 4 concentrations observed in all sulfate‐poor sediments. CH 4 concentrations in the freshwater‐influenced sediments averaged 1.34 ± 0.98 μmol g −1 , with highly depleted δ 13 C‐CH 4 values ranging from −89‰ to −70‰. In contrast, the sulfate‐affected upper 300 cm of the lagoon exhibited low average CH 4 concentrations of 0.011 ± 0.005 μmol g −1 with comparatively enriched δ 13 C‐CH 4 values of −54‰ to −37‰ pointing to substantial methane oxidation. Our study shows that lagoon formation specifically supports methane oxidizers and methane oxidation through changes in pore water chemistry, especially sulfate, while methanogens are similar to lake conditions.